1996
DOI: 10.1183/09031936.96.09091943
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic charge on a plastic spacer device influences the delivery of salbutamol

Abstract: E El le ec ct tr ro os st ta at ti ic c c ch ha ar rg ge e o on n a a p pl la as st ti ic c s sp pa ac ce er r d de ev vi ic ceABSTRACT: The aim of this study was to determine whether electrostatic charge on a plastic spacer decreases the delivery of salbutamol from a pressurized metereddose inhaler (pMDI) and, if so, to find an optimal and practical treatment to remove the charge. Ten single actuations from a salbutamol pMDI were drawn through different Volumatic® spacers at a constant flow of 60 L·min -1 . T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
6

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 8 publications
(9 reference statements)
2
63
0
6
Order By: Relevance
“…The in vitro studies confirm and extend the authors' previous work [8,10]. Coating a plastic spacer with an ionic detergent is a simple method of reducing electrostatic charge, thereby increasing the in vitro drug delivery.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The in vitro studies confirm and extend the authors' previous work [8,10]. Coating a plastic spacer with an ionic detergent is a simple method of reducing electrostatic charge, thereby increasing the in vitro drug delivery.…”
Section: Discussionsupporting
confidence: 75%
“…However, the authors' previous in vitro work [8,10] has demonstrated that detergent coating improves the delivery of salbutamol through different plastic spacers (Aerochamber1, Babyhaler1, Babyspacer1, Nebuhaler1, and Volumatic), confirming that electrostatic charge plays a major role. A low-volume metal spacer [21] has been developed to eliminate the problem of static charge, but in view of the present results and the issues of cost and availability, a simple plastic spacer may remain the device of choice worldwide.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Dolayısıyla haznelerin üretici firmanın tavsiyeleri doğrultusunda haftada bir kere yıkanması tavsiye edilir. Haznenin ilk kullanımından önce deterjanlı suyla yıkanması onda mevcut olan elektrostatik şarjı azaltacak ve cihazın tedavideki etkinliğini arttıra-caktır (25,26).…”
Section: öLçülü Doz Inhalerunclassified
“…Fakat basit ve pratik bir yöntem olan aracı tüpün yüzeyini gün-de bir iyonik deterjan ile kaplamanın akciğere ulaşan ilaç miktarını %50-70 oranında artırdığı ve akciğere giden ilaç miktarının belirlenmesinde elektrostatik yükü ortadan kaldırmanın ilaç akım hızından daha önemli olduğu ortaya konmuştur. Ayrıca, yeni kullanılmaya baş-lanan tüplerin daha fazla elektrostatik yük içermesin-den dolayı kullanımda olan eski aracı tüplere göre hastaya ulaşan ilaç miktarında anlamlı bir azalmaya neden olduğu, aracı tüpü kullandıktan sonra sadece su ile yı-kamanın elektrostatik yükü azaltmadığı ve dolayısıyla hastaya ulaşan ilaç miktarını azalttığı, aracı tüpün iç yüzeyini alüminyum folyo ile kaplamanın iyonik deterjanla maruziyete benzer şekilde elektrostatik yükü anlamlı oranda azalttığı gösterilmiştir (12,13).…”
Section: Araci Tüpunclassified